A magneto-fluorescence bacteria assay strategy based on dual colour sulfide fluorescent nanoparticles with high near-IR conversion efficiency. Issue 13 (29th May 2020) - Zhu, Yanli; Wang, Jikai; Sun, Yiyang; Cai, Qingyun
Abstract : Ultra-bright CaS and SrS fluorescent nanoprobes coupling magnetic ZnFe2 O4 nanoparticles applied in bacteria quantitative sensing and naked-eye analysis. Abstract : Anti-Stokes fluorescence induced by near-IR (NIR) radiation is particularly advantageous for the bioassay of complex samples, but most of the commonly used NIR-induced fluorescence nanomaterials such as up-conversion nanoparticles (UCNPs) do not exhibit satisfactory fluorescence intensity and work against achieving a highly sensitive bioassay. In this study, we a construct sensitive and specific bacteria biosensor based on the NIR-stimulated CaS: Eu, Sm, Mn and SrS: Ce, Sm, Mn nanoparticles. The fluorescent nanoparticles are conjugated with bacteria recognition fragments. In addition, the independent emission bands of these two types of fluorescent nanoparticles make it possible to detect and quantify Gram-positive strain and Gram-negative strain, simultaneously. Intense fluorescence and magnetic enrichment of magneto-fluorescence systems enable bacteria discrimination with the naked eye and improve sensitivity in trace bacteria detection (<20 CFU mL −1 ). The linear relationship between the fluorescence intensity and bacterial concentration is established with a detection range of 25–10 6 CFU mL −1 . Furthermore, this NIR-excited assay strategy demonstrates better anti-interference capability than UV/visible-excited assay methods, showing high potential and practical value for medical diagnostics and bacteria monitoring.